Between exclusion and emancipation: Foucault's ethics and disability - Pezdek, Krzysztof (Nursing philosophy, 2017)
The aim of the study was to demonstrate how Foucault's ethics, which we understand as a tension between exclusion and emancipation, helps both critically reassess two disability models that prevail in the contemporary literature concerning disability, that is the medical model and the social one, and support and inspire an ethical project of including people with disabilities in spheres of life from which they have been excluded by various power/knowledge regimes. We claim, following Foucault, that such a project should be informed by critical reflection on exclusion-generating forms of knowledge about people with disabilities and focused on individual ethical actions fostering self-realization and emancipation of people with disability.